Improvement of the regenerator used for cleaning the seed cotton from waste - Toshmirzayev Qodirjon Odiljonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents the results of research work on the development of a new cotton regenerator for the extraction of cotton volatiles from waste cleaners. The main distinguishing features of the design and technological process of the new cotton regenerator for the extraction of cotton volatiles from waste cleaners are described.